Surface Energy Balance Closure and Turbulent Flux Parameterization on a Mid-Latitude Mountain Glacier, Purcell Mountains, Canada - Fitzpatrick, Noel; Radić, Valentina; Menounos, Brian (Frontiers in Earth Science, 2017)
In the majority of glacier surface energy balance studies, parameterisation rather than direct measurement is used to estimate one or more of the individual heat fluxes, with others, such as the rain and ground heat fluxes, often deemed negligible. Turbulent fluxes of sensible and latent heat are commonly parameterised using the bulk aerodynamic technique. This method was developed for horizontal, uniform surfaces rather than sloped, inhomogeneous glacier terrain, and significant uncertainty remains regarding the selection of appropriate roughness length values, and the validity of the atmospheric stability functions employed. A customised weather station, designed to measure all relevant heat fluxes, was installed on an alpine glacier over the 2014 melt season. Eddy covariance techniques were used to observe the turbulent heat fluxes, and to calculate site-specific roughness values. The obtained dataset was used to drive a point ablation model, and to evaluate the most commonly used bulk methods and roughness length schemes in the literature. Modelled ablation showed good agreement with observed rates at seasonal, daily, and sub-daily timescales, effectively closing the surface energy balance, and giving a high level of confidence in the flux observation method. Net radiation was the dominant contributor to melt energy over the season (65.2%), followed by the sensible heat flux (29.7%), while the rain heat flux was observed to be a significant contributor on daily timescales during periods of persistent heavy rain (up to 20% day-1). Momentum roughness lengths observed for the study surface (snow: 10-3.8 m; ice: 10-2.2 m) showed general agreement with previous findings, while the scalar values (temperature: 10-4.6 m; water vapour: 10-6 m) differed significantly from those for momentum, disagreeing with the assumption of equal roughness lengths. Of the three bulk method stability schemes tested, the functions based on the Monin-Obukhov length returned mean daily flux values closest to those observed, but displayed poor performance on sub-daily timescales, and periods of substantial flux overestimation.